Phytochemical screening and mic determination of different extracts of ichnocarpus frutescens - M.SRUJANA,; N.LAKSHMIDEVI, (International Journal of Pharma and Bio Sciences, 2016)
In response to the emergence of multi-drug resistant organisms, the discovery of novel and more efficient antimicrobial agents is primordial. The current study was aimed at determining the MIC values of Petroleumether, Hexane, Chloroform and Ethylacetate extracts of Ichnocarpus frutescens (L). W.T. Aiton gainst Staphylococcus aureus, Klebsiella pneumoniae, Proteus mirabilis, Enterobacter aerogenes, and Streptococcus pyogenes. Phytochemical screening of the extracts was according to the described methods. Phytochemical screening of extracts reveals the presence of alkaloids, tannins, phenols and flavonoids. Flavonoids are absent in chloroform extract. Among all the tested extracts, ethyl acetate extract has shown the lowest MIC value. The MIC values of ethylacetate extract against Staphylococcus aureus, Proteus mirabilis and Klebsiella pneumoniae were found to be 256µg/mL, 128µg/mL and 512µg/mL respectively. The results of present study give baseline information for therapeutic use of Ichnocarpus frutescens.